Kontribusi Pendekatan Kultural dalam Perkembangan Lembaga Pendidikan Islam di Indonesia - Kuncoro, Anis Tyas (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
The focus of this research is to identify the role of the cultural Islamic approach in the dynamics of Islamic education development in Indonesia. This research uses a type of qualitative research in the form of a literature review. Then, a qualitative descriptive approach is used in parsing the main discussion. The research data uses references from various scientific literature relevant to the subject matter. Furthermore, data analysis in this study includes the stages of reduction, presentation, and conclusion drawing. The subject matter of this research concludes that the development of Islamic educational institutions in Indonesia is inseparable from the success of the cultural Islamic approach in encouraging the government's role in supporting the development of educational institutions. This research contributes to the importance of cultural and political approaches in the development of faith-based educational institutions.